Energetic profile of the basketball exercise simulation test in junior elite players - Latzel, R.; Hoos, O.; Stier, S.; Kaufmann, S.; Fresz, V.; Reim, D.; Beneke, R. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To analyze the energetic profile of the Basketball Exercise Simulation Test (BEST). Methods: Ten male elite junior basketball players (age 15.5 [0.6] y, height 180 [9] cm, and body mass 66.1 [11.2] kg) performed a modified BEST (20 circuits consisting of jumping, sprinting, jogging, shuffling, and short breaks) simulating professional basketball game play. Circuit time, sprint time, sprint decrement, oxygen uptake (VO2), heart rate, and blood lactate concentration (blc) were obtained. Metabolic energy and metabolic power above rest (Wtot and Ptot), as well as energy share in terms of aerobic (Waer), glycolytic (Wblc), and high-energy phosphates (WPCr), were calculated from VO2 during exercise, net lactate production, and the fast component of postexercise VO2 kinetics, respectively. Results: Waer, Wblc, and WPCr reflect 89% (2%), 5% (1%), and 6% (1%) of total energy needed, respectively. Assuming an aerobic replenishment of PCr energy stores during short breaks, the adjusted energy share yielded Waer 66% (4%), Wblc 5% (1%), and WPCr 29% (1%). Waer and WPCr were negatively correlated (-0.72 and -0.59) with sprint time, which was not the case for Wblc. Conclusions: Consistent with general findings on energy system interaction during repeated high-intensity exercise bouts, the intermittent profile of the BEST relies primarily on aerobic energy combined with repetitive supplementation by anaerobic utilization of high-energy phosphates.